Effect of diabetes in pregnancy on the newborn (1995)
Diabetes in pregnant women is an important factor affecting perinatal morbidity and mortality. Oriented to determine the effects of the diabetes in the new born, a retrospective study was performed. 35 cases of women including diabetes mellitus or gestational diabetes were reviewed. Additionaly 26 normal women were selected ramdomly to compare the variables of interest. In some variables as Apgar test, height, cephalic and thoracic perimeters in the new born were affected. No alterations in weight neither congenital malformations were detected as result of the diabetes, comparing the two groups. Because of the importance of this disease for the mother and for the new born, and special management is required looking for minimizing the risks.